An iterative method for solving fractional diffusion‐wave equation involving the Caputo–Weyl fractional derivative. Issue 2 (27th October 2020) - Derakhshan, Mohammadhossein; Aminataei, Azim
Abstract: In this paper, we propose a numerical scheme based on the iterative method for solving the fractional diffusion‐wave equation involving the Caputo–Weyl fractional derivative of order 0 < α ≤ 2 . The convergence of the approximate solutions of the fractional diffusion‐wave equation is rigourously established. Moreover, the approximate solutions of the fractional diffusion‐wave equation have been presented graphically.